Comparison of The Effectiveness of Campylobacter Growth Ability in Culture Media Added Supplements Lysed Sheep's Blood with Lysed Cow's Blood in Chicken Meat Samples - Yezzi Irmanora; Elisa Julianti; Faisal Faisal; Desriwan Angga Putra (The International Journal of Tropical Veterinary and Biomedical Research, 2023)
Blood is a good growth medium for bacteria by preventing the accumulation of toxic oxygen (peroxide and superoxide) and increasing the growth ability of these bacteria. The purpose of this study was to evaluate the ability of lysed sheep blood and lysed cow blood as a substitute for lysed horse blood on Campylobacter growth media, as well as evaluate the growth of Campylobacter from chicken meat samples on culture media supplemented with lysed sheep blood and lysed cow blood compared to the media cultures using lysed horse blood supplements. The concentration of lysed sheep blood, lysed cow blood, and lysed horse blood used was 5% each. The chicken meat samples used in this study were 30 samples. Based on the results, 14 samples of C. jejuni bacteria showed the ability to grow up to 107 and 16 samples up to 106. In the media added with lysed cow blood supplement only one sample was able to grow up to 106, 17 samples grew up to 105, and 12 samples grew up to 104. These results statistically used the one way analysis of variance (ANOVA) test indicating a significant difference significant (P0.05). Further tests using post hoc least significance different (LSD) showed a comparison of the average growth in lysed horse blood, lysed sheep blood, and lysed cow blood significantly different (P 0.05), while the average value of each treatment was the addition of lysed horse blood supplements, lysed sheep blood, and cow blood consecutive lysis was 8.551 ± 0.340, 7.117 ± 0.544, and 5.265 ± 0.548. The addition of lysed sheep blood and lysed cow blood to bolton broth media in this study can be used for C. jejuni isolation. However, the blood of lysed sheep had a higher effectiveness in the ability to grow C. jejuni, which was close to the ability to grow with the addition of lysed horse blood as a control, compared to the addition of lysed cow blood.